STRATEGY FOR SPORT SCIENCE PROGRESSIVE - Ardo Okilanda Ardo Okilanda; Firmansyah Dlis; Hidayat Humaid; Dede Dwiansyah Putra (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2019)
The objective of this research is sport science campaign to society. This research used survey qualitative method conducted to students with 90 respondents made campaign task and used Instagram actively. The survey result from student’s task of sport science campaign by using Instagram the students was divided into three categories, they were 15% students used Instagram no more than one hour, 30% used Instagram for two hours and more than 65% used Instagram more than three hours. Based on the result, students have a big effect to contribute society knowledge in sport science by using Instagram. Keywords: Community, Instagram, Sport Science